INTEGRATING ETHICAL ARTIFICIAL INTELLIGENCE IN SECONDARY EDUCATION: A FRAMEWORK FOR RESPONSIBLE DIGITAL PEDAGOGY - Ricky Ekaristy Purwadi; Asep Suhana (International Journal of Teaching and Learning, 2025)
The rapid development of artificial intelligence has brought significant transformations in the education sector, including secondary education. However, the adoption of AI without a clear ethical framework has the potential to pose risks, ranging from algorithmic bias to violations of student data privacy. This study aims to formulate a framework for responsible digital pedagogy by integrating AI ethical principles into secondary education practices. Through a literature review method, this study examines theories, policies, and global best practices related to AI ethics and its use in learning contexts. The results of the study identify five main elements in the ethical digital pedagogy framework: algorithmic transparency, data protection, access equity, ethical digital literacy, and teacher involvement as critical facilitators. This study emphasizes the need for collaboration between policymakers, educators, and technology developers to create a safe, fair, and socially responsible learning environment in the digital era. This framework is expected to be a reference in the formulation of humanistic AI-based education policies and curricula at the secondary school level.